(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
femur treated by PFNA. Methods: A prospective analytic cross-sectional study was conducted at Orthopaedic Surgery department, Dow Medical College & Dr. Ruth Pfau Civil Hospital Karachi during the period from January 2017 to May 2018. Thirty-three patients with Subtrochanteric femur fracture according to Russell and Taylor Classification Type IA & B were operated with Proximal femoral nail antirotation (PFNA). Patients were assessed clinically for functional outcome based on Harris hip score and radiologically for union. Typical post-surgical morbidity (i.e., Infection, delayed union, nonunion, mal-union and fixation failure) were noted. Multiple fractures in polytrauma patients, pathological fractures, open fractures, poor ambulatory patients previous to the fracture and related neurovascular injuries were excluded from the study. Results: A total of 33 patients (21 males, 12 females; mean age 49.5 years) were treated with PFNA. Based on Russell and Taylor classification: 18 had Type IA and 15 had Type IB fractures. The mean follow-up duration was 11 months (range, 9 to 16 months). All fractures were united in an average time of 18.4 weeks). Superficial stitch infection was seen in 5 cases. We had no instance of deep infection. Distal locking screw was broken in two patients. Implant failure and / or Nonunion were not observed whereas delayed union was noted in 5 patients. The functional outcome results were (as per Harris hip scoring system) excellent and good in 27(81.8%) and fair to poor in 6 (18%) cases. Conclusions: The post-operative clinical and radiological outcome suggest that PFNA is an exceptional device for treatment of fracture subtrochantric femur. Although technically demanding, it avoids extensive soft tissue dissection and iatrogenic bony devascularization thus decrease the incidence fracture nonunion and implant failure and at the same time provide much more axial stability due to its intramedullary placement thus it allows the patients to move relatively early following surgery.